How to fix a broken heart—designing biofunctional cues for effective, environmentally-friendly cardiac tissue engineering - Benko, Aleksandra; Webster, Thomas J. (Frontiers in Chemistry, 2023)
Cardiovascular diseases bear strong socioeconomic and ecological impact on the worldwide healthcare system. A large consumption of goods, use of polymer-based cardiovascular biomaterials, and long hospitalization times add up to an extensive carbon footprint on the environment often turning out to be ineffective at healing such cardiovascular diseases. On the other hand, cardiac cell toxicity is among the most severe but common side effect of drugs used to treat numerous diseases from COVID-19 to diabetes, often resulting in the withdrawal of such pharmaceuticals from the market. Currently, most patients that have suffered from cardiovascular disease will never fully recover. All of these factors further contribute to the extensive negative toll pharmaceutical, biotechnological, and biomedical companies have on the environment. Hence, there is a dire need to develop new environmentally-friendly strategies that on the one hand would promise cardiac tissue regeneration after damage and on the other hand would offer solutions for the fast screening of drugs to ensure that they do not cause cardiovascular toxicity. Importantly, both require one thing–a mature, functioning cardiac tissue that can be fabricated in a fast, reliable, and repeatable manner from environmentally friendly biomaterials in the lab. This is not an easy task to complete as numerous approaches have been undertaken, separately and combined, to achieve it. This review gathers such strategies and provides insights into which succeed or fail and what is needed for the field of environmentally-friendly cardiac tissue engineering to prosper.